Corporate social responsibility and firm value: Profitability as moderator in mining sector - Susilawati Susilawati; Amelia Oktrivina; Raihan Putra Yosialdi (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
This study examines the impact of Corporate Social Responsibility (CSR) on firm value, with profitability as a moderating variable, focusing on mining sector companies (oil and gas, coal, minerals, and gold) listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. Employing a quantitative approach, the research utilizes secondary data analyzed through multiple linear regression and Moderated Regression Analysis (MRA) in Jamovi, with samples selected via purposive sampling. The results demonstrate that CSR positively and significantly enhances firm value, while profitability further strengthens this relationship. These findings highlight the synergistic role of CSR and profitability in maximizing firm value, offering practical insights for mining companies to align social responsibility initiatives with financial performance to attract investor and stakeholder confidence